Model Dan Nilai Jasa Hidrologis Dalam Perlindungan Ekosistem Hutan Dan DAS - Sutopo, Muhammad Fauzi; Mawardi, Ikhwanuddin (Jurnal Teknologi Lingkungan, 2018)
ABSTRACTResearch on modeling and hydrological services in forest and watershed (DAS) ecosystem protection is still very little done in Indonesia; therefore, this research will be very useful for related stakeholders, since the purpose of the research will answer two problems, namely: (1) what factors can significantly affect the hydrological services in the protection of forest and watershed ecosystem both in the upstream and downstream areas DAS and (2) establish the economic value of hydrological services in upstream and downstream watershed areas. The results of the study indicate that: water consumption in the downstream area is strongly influenced by: (a) family expenditure at 96.5% significance level, (b) family income at 80.7% significance level, and (c) work experience at significance level 72.4% with R Square Model 53.00% validation test. Water consumption in the upstream area is influenced by: (a) the cost of water storage at the significance level of 94.4%, (b) the age of the respondent at the significance level of 71.4%, and (c) the distance to the resource (location water springs) water at a significance level of 55.7% with a validation test of R Square model 97.30%. The research in this study at the same time responds to the existence of hydrological services as a model of protection of forest ecosystems and integrated and comprehensive watersheds from upstream - downstream; economic value of ecosystem services in forest and watershed protection in the form of hydrological services, which is the value of choice from the utilization of water resources or as hydrological services, which is Rp. 1.272.211.617.235. The value of this choice is basically the sum of the Consumer Surplus in the downstream area of Rp. 830,837,758,433 and the value of Producers Surplus in the upstream area of Rp. 441.373.858.801.Keywords: hydrological services, ecosystem protection, economic value of hydrological services, upstream-downstream watershed areas, producers surplus, consumer surplus.ABSTRAK Penelitian tentang pemodelan dan jasa hidrologis dalam perlindungan ekosistem hutan dan Daerah Aliran Sungai (DAS) masih sangat sedikit dilakukan di Indonesia, sehingga penelitian ini akan sangat berguna bagi pemangku kepentingan terkait, karena tujuan penelitian akan menjawab dua masalah, yaitu: (1) faktor apa yang dapat secara signifikan mempengaruhi jasa hidrologis dalam perlindungan ekosistem hutan dan DAS baik di DAS hulu maupun di DAS hilir; dan (2) menetapkan nilai ekonomi jasa hidrologis di kawasan DAS hulu-hilir. Hasil penelitian menunjukkan: Konsumsi air di daerah hilir sangat dipengaruhi oleh: (a) pengeluaran keluarga pada tingkat signifikansi 96,5%, (b) pendapatan keluarga pada tingkat signifikansi 80,7%, dan (c) pengalaman kerja pada tingkat signifikansi 72,4% dengan uji validasi Model R2 53,00%. Konsumsi air di daerah hulu dipengaruhi oleh: (a) biaya penyimpanan air pada tingkat signifikansi 94,4%, (b) usia responden pada tingkat signifikansi 71,4%, dan (c) jarak ke sumber daya air (lokasi mata air) pada tingkat signifikansi 55,7% dengan uji validasi Model R2 97,30%. Pada saat yang sama penelitian ini menanggapi keberadaan jasa hidrologis sebagai model perlindungan ekosistem hutan dan DAS terpadu dan komprehensif dari hulu - hilir; nilai ekonomi jasa ekosistem dalam perlindungan hutan dan DAS dalam bentuk jasa hidrologis, yang merupakan nilai pilihan dari pemanfaatan sumber daya air atau sebagai jasa hidrologis, sebesar Rp. 1.272.211.617.235. Nilai pilihan atasjasa hidrologis ini pada dasarnya adalah jumlah dari Surplus Konsumen di daerah hilir sebesar Rp. 830.837.758.433 dan nilai Surplus Produser di daerah hulu sebesar Rp. 441.373.858.801.Kata kunci: layanan hidrologis, perlindungan ekosistem, nilai ekonomi dari layanan hidrologi, daerah aliran sungai hulu hilir, surplus produsen, surplus konsumen